Implementasi Program Jaminan Kecelakaan Kerja (JKK) pada BPJS Ketenagakerjaan terhadap Petugas Pemadam Kebakaran di Dinas Pemadam Kebakaran UPT. Medan Tuntungan - Karo-Karo, Andrew Winpray; S, Sintia; Angelina, Yosia Sere; Siregar, Hairani (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Work Accident Insurance (JKK) is one of the programs provided by BPJS Ketenagakerjaan aimed at ensuring that workers are protected from the potential risks of accidents or misfortune while performing their duties. The purpose of this study is to understand and describe the implementation of the Work Accident Insurance (JKK) program for firefighters at the Medan Tuntungan Fire Department (UPT). This research applies a descriptive method with a qualitative approach. To collect data, the techniques used include interviews, analysis, observation, and documentation. The results show that the implementation of the Work Accident Insurance program still faces challenges, such as the lack of understanding among firefighters about the benefits of JKK, the lack of knowledge on how to use JKK, and the insufficient cooperation between BPJS Ketenagakerjaan and the Fire Department. This study recommends further socialization and simplification of administrative procedures to enhance the effectiveness of the JKK worker protection program implementation.